Low-Frequency Raman Spectroscopy: An Exceptional Tool for Exploring Metastability Driven States Induced by Dehydration - Yannick Guinet; Laurent Paccou; Alain Hédoux (MDPI AG, 2023)
The use of low-frequency Raman spectroscopy (LFRS; ω < 150 cm−1) is booming in the pharmaceutical industry. Specific processing of spectra is required to use the wealth of information contained in this spectral region. Spectra processing and the use of LFRS for analyzing phase transformations in molecular materials are detailed herein from investigations on the devitrification of ibuprofen. LFRS was used to analyze the dehydration mechanism of two hydrates (theophylline and caffeine) of the xanthine family. Two mechanisms of solid-state transformation in theophylline were determined depending on the relative humidity (RH) and temperature. At room temperature and 1% RH, dehydration is driven by the diffusion mechanism, while under high RH (>30%), kinetic laws are typical of nucleation and growth mechanism. By increasing the RH, various metastability driven crystalline forms were obtained mimicking successive intermediate states between hydrate form and anhydrous form achieved under high RH. In contrast, the dehydration kinetics of caffeine hydrate under various RH levels can be described by only one master curve corresponding to a nucleation mechanism. Various metastability driven states were achieved depending on the RH, which can be described as intermediate between forms I and II of anhydrous caffeine.